A logística de transporte agrícola multimodal da Região Oeste paranaense - Dalmás, Sandra Regina da Silva Pinela (2008)
This research work compares the options of monomodality, intermodality and multimodality to the transport of bulk grains from the western region of Paran?. The purpose of the research was to identify the reasons for the low utilization of waterways in comparison with the highways and railways, in this region. In order to do this, were found the main features of the load transport through each of these modal ones, and the performance of the maritime ports of Santos (SP) and Paranagu? (PR), regarded as the most suitable for export such production. The data has been collected from primary sources, by the technique of in situ observation made in river and raiwayl terminals and guided unstructured interviews with some professionals responsible for the logistics of companies engaged in the marketing of grain in the region. It has been used some documentary research to gather secondary data, concerning the characteristics of transport and freight prices. The analysis of content was made through comparison between prices of freight, losses, and the impact in the costs related to the environmental costs, of each simulated arrangement. It found out that the preference in the region for road modal occurs mainly due to the lack of infrastructure logistics for the other modal ones. In the comparison of performance, the Port of Santos presents minor average time of wait to moor a ship than the Port of Paranagu?. It was concluded that the waterway is an alternative to the costs reduction of transport in the region and that there is a latent demand for joint efforts of public and private initiative to reach the solution of the existing deficiencies for the transport of agricultural production of the western region of Paran